Antifungal iridoids from the stems of Tocoyena formosa - Bolzani, Vanderlan Da Silva [UNESP]; Trevisan, Ligia Maria Vetoratto [UNESP]; Izumisawa, Clara Miti; Young, Maria Claudia Marx (Sociedade Brasileira de Quimica (SBQ), 1996)
A new antifungal iridoid compound, together with three active known iridoids, galioside, galioside aglucone, and apodanthoside, as well as 3-O-β-D-glucopyranosyl-28-O-β-D-glucopyranosyl quinovic acid and quercetin-3-O-methyl-3-O-β-D-rhamnopyranoside, were isolated from the stems of Tocoyena formosa. This new compound was characterized by spectral data as 11-O-transferuloylteucrein.
Keywords: Antifungal iridoids; Flavonol glycoside; Rubiaceae; Tocoyena formosa; Triterpene saponin